2022
DOI: 10.3390/cancers14081859
|View full text |Cite
|
Sign up to set email alerts
|

Alternatives for MRI in Prostate Cancer Diagnostics—Review of Current Ultrasound-Based Techniques

Abstract: The purpose of this review is to present the current role of ultrasound-based techniques in the diagnostic pathway of prostate cancer (PCa). With overdiagnosis and overtreatment of a clinically insignificant PCa over the past years, multiparametric magnetic resonance imaging (mpMRI) started to be recommended for every patient suspected of PCa before performing a biopsy. It enabled targeted sampling of the suspicious prostate regions, improving the accuracy of the traditional systematic biopsy. However, mpMRI i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 134 publications
(156 reference statements)
0
5
0
Order By: Relevance
“…Even in the early stages of PCa, angiogenesis causes increased flow, and CEUS can show imbalance of intraprostatic vessels and focal advancement [ 22 , 24 ]. Even though CEUS is a valid technique due to its own unique benefits, guidelines do not recommend it as a regular method for merging with MRI for the diagnosis of PCa, due to its defined and device-dependent interobserver accuracy shortcomings [ 25 , 26 ]. In addition, micro ultrasound (Micro-US) is another modality used to detect PCs.…”
Section: Introductionmentioning
confidence: 99%
“…Even in the early stages of PCa, angiogenesis causes increased flow, and CEUS can show imbalance of intraprostatic vessels and focal advancement [ 22 , 24 ]. Even though CEUS is a valid technique due to its own unique benefits, guidelines do not recommend it as a regular method for merging with MRI for the diagnosis of PCa, due to its defined and device-dependent interobserver accuracy shortcomings [ 25 , 26 ]. In addition, micro ultrasound (Micro-US) is another modality used to detect PCs.…”
Section: Introductionmentioning
confidence: 99%
“…In western countries, prostate malignant tumor is considered as the common cancer, especially in elderly men [ 1 ]. It was reported that the occurrence rate of prostate malignant tumor raised every year, which severely affected the physical and psychological status of these patients [ 2 , 3 ]. Many studies reported that patients with prostatic cancer in the early phase who underwent timely treatment could gain a more than 5-year survival rate, while those in the end stage showed an obviously less than 5-year survival rate [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Radiomics imaging approaches such as multi-parametric magnetic resonance of the prostate (mpMRI) and prostate-specific membrane antigen positron emission tomography (PSMA-PET) and new ultrasound scans are also in use for PCa screening and diagnosis 9 . As a result, crucial changes in the 2020 European Association of Urology (EAU) guidelines were established, promoting mpMRI to being recommended initially for every patient with suspicion of PCa (elevated PSA/abnormal DRE) before performing the biopsy 14 . Bourdoumis et al 15 reported a prostate-specific, non-protein coding RNA (PCA3) that is significantly overexpressed in PCa.…”
Section: Introductionmentioning
confidence: 99%